Impact of a designed isotonic exercise program on pain intensity of muscle cramps in legs of patients undergoing hemodialysis; a randomized clinical trial - Mahdi Poornazari; Khadijeh Dehghani; Sara Shahbazi; Firooz Khaledi Sardashti (Society of Diabetic Nephropathy Prevention, 2017)
Introduction: Pain due to muscle cramp is a common complication during hemodialysis. Studies have shown that exercise can reduce pain and fatigue through reduction of muscle stiffness and sensitivity, and improvement blood flow. Objectives: The aim of this study was to evaluate the impact of a designed program of isotonic exercise on pain intensity of leg muscle cramps in patients undergoing dialysis. Patients and Methods: This clinical trial was conducted on 60 patients with muscle cramps during dialysis. The participants were randomly divided into experimental and control groups. The intensity of muscular cramps and pain were recorded before and after the implementation of the exercise package. The isotonic exercise package included 10 sessions of exercise with a stationary bicycle lasting 10 minutes before hemodialysis. SPSS statistical software was used for data analysis. Descriptive statistics, t test, and analysis of variance (ANOVA) were used for comparison of means of variables. Results: The results showed a significant reduction in the severity and frequency of muscle cramps after exercise. The mean pain severity in the experimental and control groups had, respectively, differed from 8.73 ± 1.01 and 8.83 ± 1.05 before the intervention, to 4.97 ± 1.67 and 9.39±3.31 after the intervention (P < 0.001, P < 0.05). Age, sex, weight, blood pressure, round per minute (rpm) of pump, and dialysis duration showed no significant relationship with pain severity and frequency during dialysis (P > 0.05). Conclusion: The results showed that exercise dramatically decreased the severity and frequency of leg muscle cramps. Therefore, this method can be used in dialysis units.